The Effect of Arabic Language as Learning Provided Language on the Listening Skills of The Second Grade Students (Class II A) at Tarbiyatul Mu’allimin AlIslamiyah (TMI) Al-Amien Prenduan Sumenep Madura - Yakin, Ainul; Pulungan, Taufik Hidayat (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
In this research, the researcher paid attention to a learning going on in pondok pesantren Al-Amin Prenduan. In an effort to improving ability of Arabic language student in this boarding school applying various kinds of learning methods, one of them was learning methods with using Arabic as introduction of learning. In an effort to improving studentâ€™s skill in using Arabic, every teacher who was teaching must be using a methods or strategy learning, that was one of themÂ  by using Arabic as introduction of learning. Which was made a touched upon in this research towards ability of maharah istimaâ€™ (Listening)Students. In this research, Â the aim was to find out the effect of Arabic language made as introduction of learning towardsÂ  istimaâ€™ ability of studentÂ  at grade II A Marhalah Tsanawiyah TMI Al-amien Prenduan. In this case the researcher used quantitative approach by type rating scale. Population in this research were at grade II A man that is 26 Student, and the instrument in this research , the researcher used questionnaire and test, questionnaire for variable X and test for variable Y. For data analysis in this research used SPSS, by usingÂ  Ttest (simple regression test), which is to dicovered the effect of variable X towards variable Y. After doing the analysis afterwards appeared the result which was 0,05 < 0,05 / 32,069 > 1, 70562, from the result could be drawn conclusion that there was the effect of made Arabic as introduction of learning towards istimaâ€™ ability of Student at grade II A man Marhalah Tsanawiyah TMI Al-amien Prenduan. And the strong of effect Arabic as introduction learningÂ  towards istimaâ€™ ability of Student at grade II A man Marhalah Tsanawiyah TMI Al-amien Prenduan was in the amount of 7,9% and included into good category.Â